DREB1 Gene in Regulating Drought Tolerance in Cereal Plants - Todingan, Ajeng Klarica; Aprilian Pailang, Agista; Hala, Yusminah (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
This study aims to explain the role of the DREB1 gene in increasing drought tolerance in plants with an emphasis on recent advances in genetic engineering. In this research, the method used is a literature review by collecting library data, reading and taking notes, and critically managing research data related to the DREB1 gene. In this research, data analysis starts by examining the results from studies that are most relevant to the research problem. The results of the literature review obtained indicate that the DREB1 gene is a transcription factor that plays a role in regulating a number of other genes related to drought characteristics. The DREB genes participate in hormone signalling pathways and regulate proteins that interact with downstream genes to improve plant stress tolerance. When there is a drought, seedlings that have the DREB gene inserted have a survival rate of 36%, while plants without the DREB gene all die. These results indicate that the DREB1 gene is a positive regulatory gene for heat tolerance in plants. In this case, the transgenic lines keep their stomata partially closed, which helps maintain a minimum transpiration rate to cool the canopy and reduce the temperature of both the canopy and leaves. We achieve this by coordinating the control of stomata, minimising water loss, and preserving cell turgor, all of which prevent the plant from dying.